Further studies on south eastern Asian Luciolinae: 1. Sclerotia Ballantyne, a new genus of fireflies with back swimming larvae 2. Triangulara Pimpasalee, a new genus from Thailand (Coleoptera: Lampyridae) - Ballantyne, Lesley A.; Lambkin, Christine L.; Luan, Xin; Boontop, Yuvarin; Nak-Eiam, Sorasak; Pimpasalee, Suttisan; Silalom, Sommyot; Thancharoen, Anchana (Zootaxa, 2016)
Sclerotia Ballantyne gen. nov. is established for seven species. Sclerotia aquatilis (Thancharoen, 2007), Scl. brahmina (Bourgeois, 1890), Scl. carinata (Gorham, 1880), Scl. flavida (Hope, 1845), Scl. seriata (Olivier, 1891), and Scl. substriata (Gorham, 1880) are transferred from Luciola Laporte. Sclerotia fui sp. nov. from China is described as new. Luciola cingulata Olivier, 1885 is synonymised with Luciola substriata Gorham. Luciola formosana Pic, 1916 is removed from synonymy with Luciola substriata and newly synonymised with Luciola flavida (Hope). Males are characterised by linear elytral punctation, a set of three sclerites surrounding the aedeagal sheath and a light organ in ventrite 7 with emarginated anterior margin. Associated females lack bursa plates. Larvae associated for three species are back swimmers, having heavily sclerotised exoskeleton and a metapneustic respiratory system. Males and associated females are keyed. Analysis of molecular evidence for Chinese populations of three species indicates monophyly of Sclerotia Ballantyne gen. nov. and distinct separation from other genera.Triangulara Pimpasalee gen. nov. is described from Tri. frontoflava Pimpasalee gen. et sp. nov. from Thailand. It is superficially similar to Sclerotia gen. nov. but larger, and specimens in collections appear to have been confused with the similarly coloured Scl. substriata (Gorham) comb. nov. Males differ in having an elongate triangular light organ in ventrite 7 and are without sclerites around the aedeagal sheath. Larvae are not reliably associated but may be aquatic.